Identification, molecular characterization and seed transmission of phytoplasma in vegetable and fruit crops in Malaysia - Darshanie, Tennakon Mudiyanselage Nadika (2021)
Phytoplasmas are prokaryotes belong to class Mollicutes that caues diseases in more than 700 plant species including vegetables, fruits, ornamentals, cereals and forest plants worldwide. In Malaysia, phytoplasma diseases have been reported in periwinkle, coconut and ornamental palms but not in vegetable and fruit crops due lack of knowledge and research on the presence and transmission of phytoplasma in these crops. In this study, phytoplasmas were characterised and classified based on the 16SrRNA gene sequence and the seed transmission of this pathogen was tested. Samples exhibiting phytoplasma disease symptoms (34) were collected from farms in Selangor, Malaysia including pumpkin (Cucurbita moschata), bitter gourd (Momordica charantia), papaya (Carica papaya), key lime (Citrus aurantiifolia), chili (Capsicum annuum) and cucumber (Cucumis sativus). Non-symptomatic samples (20) were also collected. DNA extraction was done using CTAB method and Nested PCR was performed using universal primers, P1/ P7 and R16F2n/ R16R2 to amplify 16SrRNA gene. The amplicons generated from primer pairs R16F2n / R16 R2, were cloned and sequenced in both directions. The nucleotide sequences were assembled, edited and compared with available sequences in GenBank using blast alignment. Phylogenetic analysis by MEGA7 software using neighbour joining method done in 1,000 replicates. Virtual RFLP analysis of the F2nR2 fragments of the 16SrRNA gene was accomplished with 17 restriction enzymes; AluI, BamHI, BfaI, BstUI(ThaI), DraI, EcoRI, HaeIII, HhaI, HinfI, HpaI, HpaII, KpnI, Sau3AI (MboI), MseI, RsaI, SspI and TaqI, using iPhyClassifier software. Transmission electron microscopy on phytoplasma infected chilli leaf petiole samples were conducted to observe the presence of elliptical bodies of the phytoplasma. Seeds were collected from phytoplasma infected chili plants and were allowed to germinate under aseptic condition to test for seed transmission of phytoplasma in chili. The presence of Phytoplasma DNA in all the symptomatic samples of pumpkin, bitter gourd, chili, key lime, cucumber and papaya was confirmed by nested PCR of 16SrRNA gene. Sequence analysis indicated that the phytoplasma association with vine malformation of pumpkin (MN585898, MT742801), Chili little leaf phytoplasma (MT192345, MT780128), bitter gourd little leaf phytoplasma (MT422719) and papaya phytoplasma (MT764331) belong to Candidatus phytoplasma asteris (16SrI), while cucumber phytoplasma (MT764158) and key lime phytoplasma (MT764157) belong to Candidatus phytoplasma trifoli (16SrVI) and Candidatus phytoplasma aurantifolia (16SrII) respectively. Virtual RFLP analysis of the 16SrRNA gene fragment profiles revealed that pumpkin phytoplasma and chili little leaf phytoplasma belong to the new subgroup of 16SrI. It has been reported to infect phytoplasma in several plant species in Malaysia but this is the first report of pumpkin, chilli, bitter gourd, cucumber, key lime and papaya infected with Candidatus phytoplasma related strain in Malaysia. In addition, transmission electron microscopy showed the presence elliptical bodies in the sieve elements of phytoplasma infected chilli plant samples. Seed transmission of the phyoplasma in infected chilli plants was established. Phytoplasma DNA was detected by Nested PCR assay in 15 days old germinated chilli seedlings. Infected seedling percentage reached up to 95%. This is the first record of phytoplasma transmission in chilli through seeds.